DEBIT AIR DAN SEDIMEN MELAYANG SUNGAI KODINA DI DESA WAYURA KECAMATAN PAMONA TENGGARA KABUPATEN POSO - Melope, Aldriyangki; Harijanto, Herman; Wahid, Abdul (Universitas Tadulako, 2020)
The Kodina watershed with its river which empties into Lake Poso is one of the critical watersheds in the Poso watershed area. In addition to generating benefits that can be enjoyed by the community, changes in land use in the upstream watershed cannot be separated from the risk of land damage due to erosion, environmental pollution and flooding. The impact that is often seen is the increase in critical land, increased soil erosion and siltation (sedimentation) in the watershed area, and the occurrence of flooding in the rainy season and drought in the dry season. The purpose of this study was to determine the water discharge and the amount of floating sediment that was transported along the Kodina river. The purpose of this research is to provide information about water discharge and the amount of floating sediment production produced by the Kodina river which as a whole can help watershed managers in overcoming problems related to the hydrological aspects of the watershed area. This research was conducted for two months, from December 2015 to February 2016 at the Kodina Watershed, Poso Regency, Pamona Tenggara District. The method used in this research is a survey method, namely by taking direct measurements in the field, which includes: measuring water flow and taking water samples for analysis of floating sediment content. The results of the calculation of the data collected during the research period after being processed show that the water discharge flowing in the Kodina river cross section is 17.10 m3 / s and the amount of floating sediment transported with river water runoff is 36.53 gr / ltr. The relationship between water discharge and floating sediment discharge has a positive relationship with a correlation value of 0.895. This shows that the increase in the Kodina River Water Flow will be followed by an increase in floating sediment loads.Keywords: Water Discharge, Floating Sediment, Watershed.